2003
DOI: 10.1002/pmic.200300487
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the larval stage of the parasite Echinococcus granulosus: Causative agent of cystic hydatid disease

Abstract: We describe the preparation of Echinococcus granulosus metacestode protein extracts for two-dimensional electrophoresis (2-DE). Protoscoleces and hydatid fluid were prepared by precipitation using trichloroacetic acid (TCA) to remove nonprotein contaminants. Compared to the untreated control, TCA precipitation improved the 2-DE gel profile of the protoscoleces proteins. Comparison of 2-DE gels from insoluble and soluble fractions of the protoscoleces protein extract showed that most proteins are insoluble afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 15 publications
2
60
0
1
Order By: Relevance
“…Albumin is also suggested to exert functions similar to those in human plasma. These functions include its ability to maintain oncotic pressure, and to act as a transport protein (Chemale et al, 2003;Li et al, 2013). However, the micro-total protein level is equivalent to a very low level of approximately 1 -2 % in the human serum (Li et al, 1985), hence diffi cult to be visually identifi ed by a reagent strip test as reported in our study in HCF with viable PSs.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Albumin is also suggested to exert functions similar to those in human plasma. These functions include its ability to maintain oncotic pressure, and to act as a transport protein (Chemale et al, 2003;Li et al, 2013). However, the micro-total protein level is equivalent to a very low level of approximately 1 -2 % in the human serum (Li et al, 1985), hence diffi cult to be visually identifi ed by a reagent strip test as reported in our study in HCF with viable PSs.…”
Section: Discussionmentioning
confidence: 69%
“…Glycogen has been reported to be present in the germinal membrane and a muco-polysaccharide is reported as a major component of both the laminated membrane and the protoscolices (Chemale et al, 2003). Moreover, it is reported that the larval stage of E. granulosus conserves greater amounts of glycogen than the adult form of the parasite.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…32 Based on the biology of 14-3-3, we did not see any reason to include this antigen as a potential candidate for the present serological follow-up study. Conversely, the P29 protein first described by Gonzalez et al 29 appeared interesting by its expression being restricted to E. granulosus protoscoleces 33 and by exhibiting a good immunodiagnostic potential to detect CE in patients before surgery. 29 Our investigations now showed that a recombinant P29 also exhibits a good prognostic value in the follow-up monitoring of those cured versus non-cured CE patients who were able to develop a seropositive status against recP29 either before or shortly after diagnosis and/or initiation of a treatment protocol, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, their efficacy in the diagnosis of human hydatid disease remains low (Sarkari and Rezaei 2015). This is due to the presence of large amounts of host pro-teins in HCF reducing the specificity (Chemale et al 2003, Monteiro et al 2010. There is also a lack of standardisation of the target antigen (Sarkari and Rezaei 2015).…”
mentioning
confidence: 99%